Phylogeography and population genomics of a lotic water beetle across a complex tropical landscape. Issue 16 (31st July 2018) - Lam, Athena Wai; Gueuning, Morgan; Kindler, Carolin; Van Dam, Matthew; Alvarez, Nadir; Panjaitan, Rawati; Shaverdo, Helena; White, Lloyd T.; Roderick, George K.; Balke, Michael
Abstract: The habitat template concept applied to a freshwater system indicates that lotic species, or those which occupy permanent habitats along stream courses, are less dispersive than lentic species, or those that occur in more ephemeral aquatic habitats. Thus, populations of lotic species will be more structured than those of lentic species. Stream courses include both flowing water and small, stagnant microhabitats that can provide refuge when streams are low. Many species occur in these microhabitats but remain poorly studied. Here, we present population genetic data for one such species, the tropical diving beetle Exocelina manokwariensis (Dytiscidae), sampled from six localities along a 300 km transect across the Birds Head Peninsula of New Guinea. Molecular data from both mitochondrial (CO1 sequences) and nuclear (ddRAD loci) regions document fine‐scale population structure across populations that are 45 km apart. Our results are concordant with previous phylogenetic and macroecological studies that applied the habitat template concept to aquatic systems. This study also illustrates that these diverse but mostly overlooked microhabitats are promising study systems in freshwater ecology and evolutionary biology. With the advent of next‐generation sequencing, fine‐scale population genomic studies are feasible for small nonmodel organisms to help illuminate the effect of habitat stability on species' natural history, population structure and geographic distribution.